Impact of MRSA Transmission and Infection in a Neonatal Intensive Care Unit in China: A Bundle Intervention Study during 2014-2017. (10th July 2019) - Huang, Huiping; Ran, Jing; Yang, Jianzhou; Li, Peng; Zhuang, Guihua
Abstract : Objective. To evaluate the efficacy of bundle intervention on healthcare-associated (HA) methicillin-resistant Staphylococcus Aureus (MRSA) infection in the neonatal intensive care unit (NICU). Methods. In this study, 11, 277 infants having undergone treatment at the NICU in Xiamen, China, from January 2014 to February 2017 were recruited. We retrospectively reviewed patients' demographic and clinical information. Patients from 2014 to 2015 were treated as the control group and those from 2016 to 2017 were classified as the experimental group. Bundle intervention measures were performed, including screening for MRSA, isolation precautions, training of hand hygiene, cleaning protocols, and decontamination of isolation ward. The HA-MRSA data and compliance of infection control measures between both groups were analyzed. Results . Through bundle interventions, the compliance with the isolation of MRSA raised from 55.88% to 92.86% and hand hygiene compliance increased from 90.07% to 93.23% ( P < 0.05). The HA infection decreased from 1.87% to 1.71% ( P > 0.05) and HA detection rate of MRSA declined from 2.63‰ to 1.00‰, respectively ( P < 0.05). Conclusion. Multifaceted interventions can effectively prevent MRSA infection and transmission; this includes active surveillance, isolation precautions, increased hand hygiene compliance, environmental cleaning, and decontamination.